PENGEMBANGAN INSTRUMEN PENILAIAN (ASSESMENT) MENGGUNAKAN WONDERSHARE QUIZ CREATOR PADA MATERI KONSEP MOL SISWA KELAS X SMK NEGERI 7 PONTIANAK - Aditya Firmansyah; Dini Hadiarti; Rody Putra Sartika (Jurnal Ilmiah Ar-Razi, 2016)
ABSTRACT This study was aimed by the impractical assessment used by the teacher. Therefore, teachers need the efficient and effective assessment system to help their work, such as wonder quiz creator. This study aimed at developing the assessment instrument on the Mole Concept on the grade X students of SMK Negeri 7 Pontianak. The model used was a modified 4-D (to 3-D) Thiagarajan; definition, design, and development. The data collecting technique used were measurement, and direct and indirect communication. The study revealed that wondershare quiz creator was considered usable. The student’s positive response was strong (76,49%) and the teacher’s positive response was very strong (90%). The effectiveness obtained probability (sig) score of 0,106>0,05, which means that there was a difference of before and after the assessment instrument given. As a result, the wondershare quiz creator is considered valid and usable. It is also preferred by the students as their response are good and positive. However, it is less effective to assess the final test.Keywords: Mole Concept, development, Wondershare quiz creator